Revision of the Cretaceous shark Protoxynotus (Chondrichthyes, Squaliformes) and early evolution of somniosid sharks. (December 2022) - Feichtinger, I.; Guinot, G.; Straube, N.; Harzhauser, M.; Auer, G.; Ćorić, S.; Kranner, M.; Schellhorn, S.; Ladwig, J.; Thies, D.; Pollerspöck, J.
Abstract: Due to the peculiar combination of dental features characteristic for different squaliform families, the position of the Late Cretaceous genera Protoxynotus and Paraphorosoides within Squaliformes has long been controversial. In this study, we revise these genera based on previously known fossil teeth and new dental material. The phylogenetic placement of Protoxynotus and Paraphorosoides among other extant and extinct squaliforms is discussed based on morphological characters combined with DNA sequence data of extant species. Our results suggest that Protoxynotus and Paraphorosoides should be included in the Somniosidae and that Paraphorosoides is a junior synonym of Protoxynotus. New dental material from the Campanian of Germany and the Maastrichtian of Austria enabled the description of a new species Protoxynotus mayrmelnhofi sp. nov. In addition, the evolution and origin of the characteristic squaliform tooth morphology are discussed, indicating that the elongated lower jaw teeth with erected cusp and distinct dignathic heterodonty of Protoxynotus represents a novel functional adaptation in its cutting-clutching type dentition among early squaliform sharks. Furthermore, the depositional environment of the tooth bearing horizons allows for an interpretation of the preferred habitat of this extinct dogfish shark, which exclusively occupied shelf environments of the Boreal- and northern Tethyan realms during the Late Cretaceous. Highlights: First evidence of Protoxynotus in the Tethyan realm. Synonymy of Paraphorosoides and Protoxynotus . Protoxynotus is an early representative of the Somniosidae. Novel functional adaptation of dentition among early squaliform sharks.